Evaluation of 17 Patients With Transverse Myelitis in Terms of Clinical, Treatment and Prognosis - Murat Turhan; Faruk İncecik; Mihriban Özlem Hergün; Dinçer Yıldızdaş; Sakir Altunbaşak (Galenos Publishing House, 2019)
INTRODUCTION: In this study, it was aimed to identify the clinical findings, treatment modalities and factors affecting the prognosis of patients who were followed up and treated with acute transverse myelitis. METHODS: A total of 17 patients diagnosed and treated with acute transverse myelitis between 2006 and 2016 were evaluated in Child Health and Diseases Services. RESULTS: Nine (52.9%) of the patients were boy, 8 (47.1%) were girl and the mean age was 9,24 +- 4,16 years. The complaints of the cases observed in the application; 16 patients (94.1%) had weakness and 1 patient (5.9%) had numbness in the feet. Twelve (70.6%) of the 17 patients had prior history of infection. Upper respiratory tract infections and gastrointestinal system infections were found in 7 (58.3%) and 5 (41.7%) cases respectively. Gender, presence of infection, type of infection, cranial nerve involvement, presence of autonomic symptoms, and treatment were not found to be prognostic. The duration of ICU stay in intensive care unit was 4.47 +- 6.79 days and the total length of stay in hospital was 17.59 +- 12.01 days. It was seen that the need for respiratory support increased the total length of stay in patients, intensive care and hospital. DISCUSSION AND CONCLUSION: Prognosis is generally good in childhood with acute transverse myelitis cases. We have not found an effective factor on prognosis in our study. There is a need for extensive research to determine prognostic factors.